Is the unitary competence hypothesis tenable? - Sulistyo, Gunadi Harry (citeus, 1994)
In Oller’s view (1979), the idea that language can be broken down into smaller, isolated segments falls short of validity. Instead, Oller hypothesizes the existence of a single faculty responsible for all language processing. Although his proposal is derived from several studies, this does not provide sufficient assurance for the validity of the theory he seeks to establish.